Prediction and analysis of components and functions of Ixeris chinensis based on network pharmacology and molecular docking - Ni, Ziwei; Ma, Zhe; Qiao, Xiaoting; Guo, Yaqian; Ruan, Cailian; Wang, Yayun; Yang, Ying (Frontiers in Medicine, 2024)
Background It is reported that the Ixeris chinensis has high medicinal value, but there are few reports about its potential molecular mechanism. We used a network pharmacology approach to predict the active ingredients, targets of action and possible interventions in diseases of Ixeris chinensis. Methods We employed various databases and software to predict the active ingredients, target genes, protein interactions, signaling pathways, network diagrams, and molecular docking of Ixeris chinensis. Simultaneously, we searched multiple Chinese and English databases and conducted meta-analyses of five randomized controlled trials. Results The analysis results revealed 12 effective components, including apigenin β-sitosterol, baicalin, baicalein, and luteolin; and selected 40 key targets, including AKT1, TNF, EGFR, ESR1, SRC, among others. GO analysis generated 225 biological processes, 39 cellular components, and 65 molecular functions; KEGG analysis revealed 103 signaling pathways. Molecular docking results indicated that the main active components of Ixeris chinensis can bind well with key targets. Five randomized controlled trials were included. Meta-analysis showed that Ixeris extract can effectively reduce animal blood lipid levels. Conclusion This study revealed the main active ingredients and key targets of Ixeris chinensis, analyzed the signaling pathways of potential targets, conducted disease prediction, and performed molecular docking prediction, providing a basis for research on the pathways of Ixeris treatment for related diseases and subsequent new drug development.